Repercussions of overturning Roe v. Wade for women across systems and beyond borders - Karine Coen-Sanchez; Bassey Ebenso; Ieman Mona El-Mowafi; Maria Berghs; Dina Idriss-Wheeler; Sanni Yaya (BMC, 2022)
Abstract June 24th, 2022, a day that will be etched in today and future generations' textbooks as a historic day, the United States of America revoked the constitutional right to seek safe abortion care. Overturning Roe v Wade allowed the divided individual states to independently decide the legal parameters regarding abortion care. A decision that disproportionately effects the reproductive lives of women residing on the land of America. Given the systemic impacts of racism, neoliberalism and white supremacy, it is the Black, racialized and poor women who suffer terrible repercussions. In this commentary the authors begin by discussing the historical biopolitical perspective, colonial systems and longstanding impacts on racialized women's bodies in America. The discussion transitions to the implications of geopolitics at play nationally and cascading impacts globally, focusing on humanitarian and emergency settings. Using a medical humanities perspective, authors highlight the collision between politics and reproductive health policy and its implications on social determinants of health, such as women's education, employment, housing, racial and gender equity and wellbeing. Long standing advocates, community leaders and healers, leading scientists, birth attendants, doctors, nurses, allied health professionals/providers and humanitarian workers - and many others - are reminded and live the weight of the continuous battle of population control, stemming from the oppressive history of control and exploitation.